How Does the Patient React After Reading the Informed Consent Form of a Gynecological Surgery? A Qualitative Study - Amorim, Andrea Cristina; Santos, Luis Guilherme Teixeira dos; Poli-Neto, Omero Benedicto; Brito, Luiz Gustavo Oliveira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To analyze the reaction of women after reading the Informed Consent Form (ICF) before undergoing elective gynecological/urogynecological surgeries.Methods A qualitative study with 53 women was conducted between September 2014 and May 2015. The analysis of the content was conducted after a scripted interview was made in a reserved room and transcribed verbatim. We read the ICF once more in front of the patient, and then she was interviewed according to a script of questions about emotions and reactions that occurred about the procedure and her expectations about the intra- and postoperative period.Results The women had a mean age of 52 years, they were multiparous, and most had only a few years of schooling (54.7%). The majority (60.4%) of them had undergone urogynecological surgeries. Hysterectomy and colpoperineoplasty were the most frequent procedures. Ten women had not undergone any previous abdominal surgery. Fear (34.6%) was the feeling that emerged most frequently from the interviews after reading the ICF, followed by indifference (30.8%) and resignation (13.5%). Nine women considered their reaction unexpected after reading the ICF. Three patients did not consider the information contained in the ICF to be sufficient, and 3 had questions about the surgery after reading the document.Conclusion Reading the ICF generates fear in most women; however, they believe this feeling did not interfere in their decision-making process.
Keywords: qualitative study; informed consent; decision-making process; elective surgical procedures